Acute Joint Blockage due to Abrasion-Related Dislocation of a Silastic Radial Head Prosthesis: A Histological Examination after 14 Years of Durability - Heinz-Lothar Meyer; Christina Polan; Anke Bernstein; Benedikt Abel; Manuel Burggraf; Marcel Dudda; Max Daniel Kauther (Case Reports in Orthopedics)
The implantation of a radial head prosthesis can take place as a therapeutic option after radial head fracture. There are various implants for this purpose. Many studies and case reports about silastic radial head prosthesis implantation describe foreign body reactions with accompanying synovitis and poor functional results. A few studies have investigated the reason for the material failure and the accompanying synovitis. The case report presented shows an unusually long durability of an in situ 14-year silastic radial head prosthesis. 14 years after implantation, a previously full-time working and healthy patient presented himself with a dislocation of the silastic radial head prosthesis and atraumatic joint blockage of the right elbow triggered by a negligible movement. The prosthesis was removed surgically. We found a macroscopic foreign body reaction intraoperatively. In a histopathological examination, with hematoxylin and eosin staining (HE) in 40x and 100x magnification, we have seen an aseptic inflammatory response to foreign bodies with activated epithelial cells and multinucleated giant cells with intracytoplasmic foreign material. Due to these problems, the silastic radial head prosthesis is no longer used today. However, there are still patients with the implanted silastic radial head prosthesis, which should therefore be checked regularly. A metal prosthesis also does not seem to be an optimal alternative due to cartilage wear and loss of ROM. The choice of prosthesis material should be selected carefully and patient-specific in radial head prosthetics according of the results presented.